2003
DOI: 10.1039/b308694a
|View full text |Cite
|
Sign up to set email alerts
|

First in-situ SAXS studies of the mesostructuration of spherical silica and titania particles during spray-drying process

Abstract: Meso-organisation of SiO2 and TiO2 particles prepared by spray drying have been for the first time analysed through in-situ SAXS. Both processing and chemical parameters are critical to obtain meso-organised spheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 8 publications
4
70
0
Order By: Relevance
“…[ 105-107 , 112 , 113 ] For silica, organosilica, alumina, aluminosilicates, titania based mesoporous materials these chemical and processing parameters have been extensively studied through the use of both ex situ and in situ characterization techniques. [ 53 , 54 ] Indeed, Boissiere et al [ 53 ] have demonstrated for the fi rst time through in situ SAXS measurements that meso-organisation of spray dried SiO 2 and TiO 2 microparticles is determined by both chemical (concentration, hydrolysis ratio, ageing time) and processing parameters (drying time). The temperature start of the organisation is strongly dependant on these parameters, since droplet concentration and gas temperature governs the evaporation/diffusion and thus the time realated system local composition.…”
Section: Main Chemical and Processing Parameters Controlling Structurmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 105-107 , 112 , 113 ] For silica, organosilica, alumina, aluminosilicates, titania based mesoporous materials these chemical and processing parameters have been extensively studied through the use of both ex situ and in situ characterization techniques. [ 53 , 54 ] Indeed, Boissiere et al [ 53 ] have demonstrated for the fi rst time through in situ SAXS measurements that meso-organisation of spray dried SiO 2 and TiO 2 microparticles is determined by both chemical (concentration, hydrolysis ratio, ageing time) and processing parameters (drying time). The temperature start of the organisation is strongly dependant on these parameters, since droplet concentration and gas temperature governs the evaporation/diffusion and thus the time realated system local composition.…”
Section: Main Chemical and Processing Parameters Controlling Structurmentioning
confidence: 99%
“…When fi lms prepared by dip or spin coating at ambient temperature adopt 2D hexagonal, 3D hexagonal, 3D cubic or lamellar structures depending on the solution composition and the humidity of the evaporation atmosphere. This difference is likely to come from the evaporation conditions of spray drying which is achieved in a hot and dry atmosphere (structuration takes place at temperature near the boiling point of the solvent and is very fast if compared with fi lms structuration conditions) [ 53 ] and modifi es the thermodynamic pseudoequilibrium of the formed mesostructure. As a general trend, the EISA process starts at the droplet/air interface where inorganic and surfactant concentrations are the highest.…”
Section: Use Of a Single Structuring Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the classical preparation process involves two main steps, precipitation and autoclaving, which are time consuming and for which operating parameters are rather difficult to control. During the last 10 years, other synthesis processes have been studied, especially processes involving Evaporation Induced Self-Assembly (EISA) [10][11][12]. However, to our knowledge, despite the very attractive potential of EISA to obtain mesostructured objects, this process has not yet been used to develop highly acidic aluminosilicate mesostructured solids.…”
Section: Mesostructured Aluminosilicate Materialsmentioning
confidence: 99%
“…As far as the last point is concerned, Boissière et al [5] used time-resolved in-situ SAXS to determine the required conditions for the mesophase to form. Regarding applications, spherical shaping and possibility to embed maghemite nanoparticles within a mesoporous silica matrix readily showed an interest in combined applications like drug delivery and magnetic resonance imaging [6] while catalysis was rather explored in presence of Pd nanoparticles [7] and nanowires [8].…”
mentioning
confidence: 99%